2012
DOI: 10.1111/j.1467-8551.2012.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Marketing Strategies and Performance: The Effects of Market Uncertainty and Strategic Feedback Systems

Abstract: Although many process‐based studies appear in the strategic management literature, little attention has been devoted to the formation process of marketing strategies. Drawing on enactment and information‐processing theories, this study views the external environment as a source of information (i.e. enacted) and organizations as information‐processing entities. We propose a conceptual framework of antecedents and market performance consequences of emergent marketing strategies and test it with a sample of 214 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 137 publications
(211 reference statements)
1
43
0
1
Order By: Relevance
“…This research provides the first quantitative study from a project portfolio perspective to complement earlier studies that explore the phenomenon of emergent strategies and related strategic management practices (Burgelman, 1994;Chari et al, 2014;Mirabeau and Maguire, 2014;Thomas and Ambrosini, 2015). The results of this study contribute to the literature in three primary ways.…”
Section: Theoretical Implicationsmentioning
confidence: 65%
See 1 more Smart Citation
“…This research provides the first quantitative study from a project portfolio perspective to complement earlier studies that explore the phenomenon of emergent strategies and related strategic management practices (Burgelman, 1994;Chari et al, 2014;Mirabeau and Maguire, 2014;Thomas and Ambrosini, 2015). The results of this study contribute to the literature in three primary ways.…”
Section: Theoretical Implicationsmentioning
confidence: 65%
“…In today's volatile and unforgiving competitive environment, it might be the emergent strategic processes that are particularly relevant for organizational adaptability and survival (Chari et al, 2014;Hamel, 2009;Thomas and D'Aveni, 2009;Whittington et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The strategic integration of other organizational functions including sales, distribution and customer service has also been exposed as a major difficulty in many organizations, further serving to diminish the strategic nature of marketing practice (Chari et al, 2012). Studies are also needed which explore the extent to which marketing decision-making is being affected by the erosion of control over data insight and analytics that is evident in many organizations.…”
Section: The Evolution Of Marketing Decision-makingmentioning
confidence: 99%
“…Despite considerable research on making strategic (important, novel and resource hungry) decisions and the characteristics of these processes (Hickson et al, 1986;Whittington et al, 2011), there is little research on how BD has influenced the way decisions are made, on the impact of data proliferation on strategic responsibilities (Chari et al, 2012;Quinn et al, 2016), or on how these data are handled at board level (Nutt & Wilson, 2010). A previous empirical study (Hickson et al, 2003) has identified the 'knowledge base' used by UK senior managers to inform their strategic decisionmaking as the single most important factor in the decision's success.…”
Section: Introductionmentioning
confidence: 99%